2014
DOI: 10.1259/bjr.20140184
|View full text |Cite
|
Sign up to set email alerts
|

Platelet factor 4 protects bone marrow mesenchymal stem cells from acute radiation injury

Abstract: Dr Lan Yang and Dr Ying-Min Liang contributed equally to this workObjective: The aim of this study was to find a new radiation protector, platelet factor 4 (PF4) and to identify its effect on haemopoietic microenvironment in vitro and in vivo. Methods: Radiation damage on bone marrow mesenchymal stem cells ex and in vitro was set up as models. Growth curve analysis, clonogenic survival assay, FACSCalibur™ (BD Immunocytometry Systems, San Jose, CA), 5-ethynyl-29-deoxyuridine immunofluorescence staining and quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…How PF4 exerts it effects on the embryos is yet unknown, but it has been reported that PF4 treatment of mesenchymal cells enhanced proliferation and apoptosis inhibition by the induction of differential expression of genes related to DNA reparation and cell cycle modulation [12]. In addition, PF4 supplementation during culture is involved in an increase in hematopoietic progenitor cell survival and differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…How PF4 exerts it effects on the embryos is yet unknown, but it has been reported that PF4 treatment of mesenchymal cells enhanced proliferation and apoptosis inhibition by the induction of differential expression of genes related to DNA reparation and cell cycle modulation [12]. In addition, PF4 supplementation during culture is involved in an increase in hematopoietic progenitor cell survival and differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…To build on this point, it has been demonstrated that platelet factor 4 (PF4), which is a peptide member of the C-X-C chemokine family (also known as CXCL4), enhances hematopoietic stem cell survival [10] and hematopoietic stem cell differentiation into B cell lineage cells through STAT5 activation [11]. PF4 has also shown effects on bone marrow mesenchymal stem cells, protecting these cells from radiation injury and modulating the expression of genes related to the cell cycle and inhibition of apoptosis [12]. These actions in poorly differentiated cells led us to suspect that PF4 exhibits positive effects over embryonic cells.…”
Section: Introductionmentioning
confidence: 99%
“…FGF-2 is upregulated in the damage cerebellum to initiate neovascularization and facilitate neurogenesis [37] . Likewise, CXCL-14 may stimulate the proliferation, chemotaxis, and tube formation of endothelial cells and are essential for the development of blood vessels [38] . We speculate that some other cytokines and growth factors beyond the 174 that we assessed may also protect SCA1 cerebella.…”
Section: Discussionmentioning
confidence: 99%
“…Although contradictory results exist in clinical studies investigating PF 4 levels in various types of cancer (53)(54)(55), to the best of our knowledge no clinical studies have focused on the changes in plasma PF 4 levels associated with RT. A number of in vitro studies have provided evidence of the protective effect of PF 4 against the damaging effect of radiation (56,57).…”
Section: Discussionmentioning
confidence: 99%